2014
DOI: 10.3390/su6107311
|View full text |Cite
|
Sign up to set email alerts
|

Thermal and Daylighting Performance of Energy-Efficient Windows in Highly Glazed Residential Buildings: Case Study in Korea

Abstract: Cooling load in highly glazed residential building can be excessively large due to uncontrolled solar energy entering the indoor space. This study focuses on the cooling load reduction and changes in the daylighting properties via the application of a double window system (DWS) with shading with various surface reflectivities in highly glazed residential buildings. Evaluation of thermal and daylighting performances is carried out using simulation tools. The reductions in cooling load and energy cost through th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…Previous work in this domain has shown that buildings can be sensitive to changes in specific design parameters based on the local climate. Factors including WWR (Chen, Yang, & Wang, 2017), (Xie, Xue, Mak, & Liu, 2017), ( Tibi & Mokhtar, 2014) , (Yu, Tian, Yang, Xu, & Wang, 2013), ], ventilation strategies (Hachem-Vermette, 2018), , (Al-Tamimi & Fadzil, 2012), (Chan & Chow, 2010), (Leigh, Bae, & Ryu, 2014), glazing materials, ( Tibi & Mokhtar, 2014), (Zhao, Künzel, & Antretter, 2015), (Yasar & Kalfa, 2012), (Cheung, Fuller, & Luther, 2005), (Bojic, Yik, & Sat, 2002), external shading (Cheong, Kim, & Leigh, 2014), (Al-Tamimi & Fadzil, 2012), , (Yik & Bojic, 2006), (Cho, Yoo, & Kim, 2014) and envelope infiltration (Carlsson, Touchie, & Richman, 2017), (Kosonen, Juha, Ilari, & Koikkalaninen, 2017), (McKeen & Fung, 2014), (Yik & Bojic, 2006) were among the most common parameters that influence a building's energy performance.…”
Section: Energy Performancementioning
confidence: 99%
“…Previous work in this domain has shown that buildings can be sensitive to changes in specific design parameters based on the local climate. Factors including WWR (Chen, Yang, & Wang, 2017), (Xie, Xue, Mak, & Liu, 2017), ( Tibi & Mokhtar, 2014) , (Yu, Tian, Yang, Xu, & Wang, 2013), ], ventilation strategies (Hachem-Vermette, 2018), , (Al-Tamimi & Fadzil, 2012), (Chan & Chow, 2010), (Leigh, Bae, & Ryu, 2014), glazing materials, ( Tibi & Mokhtar, 2014), (Zhao, Künzel, & Antretter, 2015), (Yasar & Kalfa, 2012), (Cheung, Fuller, & Luther, 2005), (Bojic, Yik, & Sat, 2002), external shading (Cheong, Kim, & Leigh, 2014), (Al-Tamimi & Fadzil, 2012), , (Yik & Bojic, 2006), (Cho, Yoo, & Kim, 2014) and envelope infiltration (Carlsson, Touchie, & Richman, 2017), (Kosonen, Juha, Ilari, & Koikkalaninen, 2017), (McKeen & Fung, 2014), (Yik & Bojic, 2006) were among the most common parameters that influence a building's energy performance.…”
Section: Energy Performancementioning
confidence: 99%
“…People are spending more and more time indoors and losing outdoor direct contact with the sun's rays. The importance of daylight consists of three basic dimensions' the field of health, the field of performance, and the feeling of well-being [1,2]. The "Indoor Generation" is taking the health risk of spending more time inside.…”
Section: Introductionmentioning
confidence: 99%
“…These phenomena generate the increase of the ambient temperature in urban areas by modifying local microclimate [20,21] and consequently building energy consumption. Increased urban temperatures, modified radiation balance, different wind speeds, and altered solar gains have a huge impact on building energy production and consumption [22,23]. For this reason, the use of commonly available typical weather data sets for predicting buildings' energy demand through numerical analysis, such as the widely used Typical Meteorological Year (TMY2) [24], the International Weather for Energy Calculation (IWEC) or the Test Reference Year (TRY), could leads to misleading decision-making process in quantifying energy efficiency in buildings located in different areas [25].…”
Section: Introductionmentioning
confidence: 99%